The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/fst.41717
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of aqueous enzymatic extraction of oil from shrimp processing by-products using response surface methodology

Abstract: The aqueous enzymatic extraction (AEE) of oil from shrimp processing by-products was investigated. Four kinds of proteases, including alkaline protease, neutral protease, flavor protease and compound protease, were applied to hydrolysis shrimp processing by-products. The results showed that flavor protease was the best hydrolysis enzyme for shrimp processing by-products to obtain high oil recovery. The influences of four factors, including enzyme amount, liquid/solid ratio, hydrolysis time and hydrolysis tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Plant cell walls are made up of lignocellulosic, and other polymers intertwined with each other, which provide a barrier to extraction of its components [35]. Enzymes are used for the digestion of these cellular materials and disruption of pores as a pre-extraction step which eases the diffusion of the oil into the extraction medium [36,37]. Some of the most effective enzymes used are from the fungus Trichoderma [38].…”
Section: Enzyme Assisted Extraction (Eae)mentioning
confidence: 99%
See 2 more Smart Citations
“…Plant cell walls are made up of lignocellulosic, and other polymers intertwined with each other, which provide a barrier to extraction of its components [35]. Enzymes are used for the digestion of these cellular materials and disruption of pores as a pre-extraction step which eases the diffusion of the oil into the extraction medium [36,37]. Some of the most effective enzymes used are from the fungus Trichoderma [38].…”
Section: Enzyme Assisted Extraction (Eae)mentioning
confidence: 99%
“…The use of response surface methodology in food science has increased in recent years [36,42,62]. During optimization a second order polynomial is developed to model the responses and data obtained from optimization is sometimes subjected to simple ANOVA, t-test [36], and/or to some free or commercial statistical packages ( Table 2).…”
Section: Types Of Software Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction efficiency of AEE on some oilseeds materials such as soybean, peanut, sesame, and Moringa oleifera, as well as shrimp by-product has been reported as higher (Liu et al 2020;Wenwei et al 2019;Mat Yusoff et al 2016;Mat Yusoff et al 2015;Latif and Anwar 2011). Enzymes could hydrolize the cell wall of oil bearing materials releasing oil to the system (Liu et al 2020;Mat Yusoff et al 2016;Mat Yusoff et al 2015;Li et al 2011;Latif and Anwar 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The use of enzyme in an AEE process has some advantages including being environmentally friendly, inexpensive because of the use of water as solvent, easy to separate, and finally, having better appearance and taste of the oil product (Mat Yusoff et al 2015). Moreover, valuable materials contained in the residue such as protein and carbohydrate could be used for other food purposes (Wenwei et al 2019). Latif and Anwar concluded that the protein which is also extracted in the AEE process has better quality and could be used for human consumption (Latif and Anwar 2011).…”
Section: Introductionmentioning
confidence: 99%